PROSZĘ O SZYBKĄ ODPOWIEDŹ DAJE NAJ I 100 PKT
Zapisz w jak najprostszej postaci: x ( x - 1 - ( 1 - x ))



Odpowiedź :

x-(x-(1-x)x) =x -(x-x+x^2) = x-x^2 =x(1-x)

x-(x-(1-x)x) =x -(x-x+x^2) = x-x^2 =x(1-x)

x-(x-(1-x)x) =x -(x-x+x^2) = x-x^2 =x(1-x)

x-(x-(1-x)x) =x -(x-x+x^2) = x-x^2 =x(1-x)

x-(x-(1-x)x) =x -(x-x+x^2) = x-x^2 =x(1-x)

x-(x-(1-x)x) =x -(x-x+x^2) = x-x^2 =x(1-x)

x-(x-(1-x)x) =x -(x-x+x^2) = x-x^2 =x(1-x)

x-(x-(1-x)x) =x -(x-x+x^2) = x-x^2 =x(1-x)

x-(x-(1-x)x) =x -(x-x+x^2) = x-x^2 =x(1-x)

x-(x-(1-x)x) =x -(x-x+x^2) = x-x^2 =x(1-x)